2013
DOI: 10.1515/psicl-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

A-prefixing in Civil War letters from Northwestern South Carolina: Constraints, individual and community grammars

Abstract: The present study deals with the process of a-prefixation in the mid-nineteenth-century dialect(s) of a selected part of South Carolina. This phenomenon is said to have been brought to America with immigrants from the southern parts of Great Britain. For the purpose of the study, a corpus of Civil War letters has been compiled in such a way as to assure at least relative geographical and social homogeneity. Specifically, letters written by soldiers of the rank of private hailing from three counties located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…It has been suggested that a-prefixing in North America has its roots in verbal noun constructions of Scottish Gaelic (Dietrich, 1981). A form discovered in civil war letters written by a South Carolinian has been proposed to hint at an influence from Ulster, Ireland (Dylewski, 2013). The preponderance of evidence, however, suggests a-prefixing arrived in North America with migrants from Southern England (Montgomery, 1995(Montgomery, , 2009.…”
Section: Excursus On History Of A-prefixing In Southern Appalachiamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a-prefixing in North America has its roots in verbal noun constructions of Scottish Gaelic (Dietrich, 1981). A form discovered in civil war letters written by a South Carolinian has been proposed to hint at an influence from Ulster, Ireland (Dylewski, 2013). The preponderance of evidence, however, suggests a-prefixing arrived in North America with migrants from Southern England (Montgomery, 1995(Montgomery, , 2009.…”
Section: Excursus On History Of A-prefixing In Southern Appalachiamentioning
confidence: 99%
“…It has been suggested that a‐ prefixing in North America has its roots in verbal noun constructions of Scottish Gaelic (Dietrich, ). A form discovered in civil war letters written by a South Carolinian has been proposed to hint at an influence from Ulster, Ireland (Dylewski, ).…”
Section: Introductionmentioning
confidence: 99%
“…Formulaic expressions in earlier correspondence have long been subject of scholarly interest; however, these have mainly been looked at from epistolary or pragmatic perspectives (e.g., Nevalainen -Raumolin-Brunberg 1995;Tieken-Boon van Ostade 1999;Fairman 2000;Nevala 2007;Bijkerk 2007;Chaemsaithong 2012), but for Dylewski (2013), who devotes a section of his monograph to "unorthodox -s" found in his corpus of Civil War letters and Pietsch (2015), who briefl y focuses on the obsolescent but remains in Irish emigrant correspondence. Finally, Meurman-Solin (2007 and mentions -s on remain in passing while discussing relatives in Scottish correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…The grammaticality of formulaic expressions present in earlier correspondence seems thus understudied; this paper aims at fi lling, at least partially, this gap. It builds on Dylewski's (2013) study and focuses on the two types of closings depicting alleged violation of agreement between subject and verb 1 attested by him in the semi-literate Confederate writings; more specifi cally, conventionalized closing formulae in which the verb remain 2 appears: "I/we remain(s) yours/your (loving, humble, etc. )…" and "(nothing/no more at present), but/so/also/and/only remain(s) your…" 3 and in which variability between -s and -Ø is observable.…”
Section: Introductionmentioning
confidence: 99%
“…Robert K. MERTON, Éléments de théorie et de méthode sociologique, Paris, Armand Colin, 1997.posées à l'utilisation de la notion, fait qu'elle apparaît, notamment au travers du sentiment d'appartenance (une « communalisation », chez Weber45 ), tantôt comme une unité virtuelle 46 , comme une illusion 47 ou comme une croyance48 .Apprendre le breton, c'est « faire société ». Selon la définition qu'en propose Simmel49 , il y a « une société partout où des hommes se trouvent en réciprocité d'action et constituent une unité permanente ou passagère ». Cette société, en tant que groupe composé lui-même de groupes50 est visible au travers du développement de l'éducation scolaire en breton, mais également dans différentes déclinaisons artistiques, littéraires, médiatiques, et parfois même dans l'innovation technologique, comme c'est le cas pour la création d'applications spécifiques et le développement des réseaux sociaux numériques en breton.Si le chef d'escadron Malbrancke avait appris le breton, il aurait pu découvrir cette société qui se fait dans la complexité et parfois dans l'opposition, entre l'héritage d'une langue ancienne et la vivacité autour de laquelle s'organise le breton au XXI e siècle notamment dans les domaines de la création artistique (musique, chant, danse, théâtre, littérature…) et de l'activité associative autour de l'enseignement, de la culture et des médias.…”
unclassified